Penerapan Keselamatan dan Kesehatan Kerja Masyarakat Sekitar Ring Satu Industri Besar di Kelurahan Bontoa - Husain, Fahrisal; Umar, Risa Bernadip; Idhan, Muhammad Arif; Bunga, Ruth Bunga; Alhabsy, Gina Audina; Rafiuddin, Rafiuddin (ADPERTISI, 2023)
Bontoa Village is an industry ring area so it has access to industry, both cement and other industries. Many community members earn their livelihood by working in industrial areas, so efforts must be made to promote occupational safety and health. The aim of outreach activities is to increase the ability to prevent early access to unwanted accidents. The method of this activity is lecture and question and answer. Before the lecture there was a pretest and after that a posttest was held. Participants in this activity are people at high risk of being affected by accidents and occupational health in Bontoa Village. The results of this activity show an increase in knowledge based on post-counseling practice. Therefore, it is recommended to carry out community service activities in other areas so that zero accidents occur.